2010
DOI: 10.1148/radiol.2541081672
|View full text |Cite
|
Sign up to set email alerts
|

Minor Head Injury: CT-based Strategies for Management—A Cost-effectiveness Analysis

Abstract: Selecting patients with MHI for CT renders cost savings and may be cost-effective, provided the sensitivity for the identification of patients who require neurosurgery is extremely high. Uncertainty regarding long-term functional outcomes after MHI justifies the routine use of CT in all patients with these injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 47 publications
0
79
0
2
Order By: Relevance
“…A flow chart describing the process of identifying relevant literature can be found in Appendix 10. A total of three studies [162][163][164] were identified as meeting the inclusion criteria. Although, no UK cost-effectiveness studies were found, one study 162 did repeat the analysis using UK modelling recommendations.…”
Section: Results Of Cost-effectiveness Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A flow chart describing the process of identifying relevant literature can be found in Appendix 10. A total of three studies [162][163][164] were identified as meeting the inclusion criteria. Although, no UK cost-effectiveness studies were found, one study 162 did repeat the analysis using UK modelling recommendations.…”
Section: Results Of Cost-effectiveness Reviewmentioning
confidence: 99%
“…However, both the Smits et al 162 and Stein et al 163 studies agreed that the CCHR prediction tool was cost-effective compared with other strategies, although the comparator strategies used were different in these studies.…”
Section: Cost-effectiveness Review Summarymentioning
confidence: 94%
See 1 more Smart Citation
“…Computed tomography (CT) is widely accepted as an effective method to diagnose and detect rare but clinically significant in patients suffering minor head injury or brain disease. As such, it has been increasingly utilized as a simple and available test for these patients (12). However, a seminal study conducted by Brenner and Hall (13) warns against its bad effects (particularly for children) due to the radiation exposure associated with CT.…”
Section: Description Of the Articles Includedmentioning
confidence: 99%
“…However, a seminal study conducted by Brenner and Hall (13) warns against its bad effects (particularly for children) due to the radiation exposure associated with CT. Independent CT imaging studies (12,14,15) advocate the adoption of a comprehensive approach that targets physicians' education to decrease the over-reliance on CT imaging for those suffering from brain disease. Therefore, to reduce the harmfulness of CT, it can be beneficial to use data mining methods specially, NBN as a predictor.…”
Section: Description Of the Articles Includedmentioning
confidence: 99%